Peran Optimasi Kepala Sekolah Dalam Peningkatan Kompetensi Profesional Guru - Sindy Sataroh; Fitri Nur Mahmudah (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2023)
This research aims to understand the role of school principals in developing teachers' professional skills. The research method employed is a qualitative approach, utilizing data collection techniques through interviews with two informants and involving documentation. The data analysis process includes stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate the role of the school principal as an educator by providing support, advice, input, setting a good example, creating a school climate, and providing training for teachers. As a manager, the school principal can engage in school management and human resource empowerment. As an administrator, the school principal handles the operational management of the school and collaborates with others. In the role of a supervisor, the school principal assesses teachers' performance. As a leader, the principal establishes intensive communication and provides mentoring for teachers. As a motivator, the principal at SD Muhammadiyah Sokonandi provides motivation, support, and work environment management.